Parking Occupancy Detection Using Convolutional Neural Networks - Brahmaiah, Shaik; Rao, K N Brahmaji (International Journal of Computer Sciences and Engineering, 2025)
Sophisticated world has the gifted man not only with comforts but also with many problems, one of the unavoidable and the most challenging problem is vehicle parking problem. The unregulated parking system is leading to huge traffic and accidents. Parking the vehicle in the parking space is highly unorganized and people have to manually check for the vacant places for parking their vehicles. So most of the people will park their vehicles in empty spaces or on the road which increases the problem further. In recent years, a lot of papers have been published addressing this issue. However, implementing them is highly expensive due to their usage of the costly sensor technology and other hardware requirements. But this paper proposes an intelligent parking system for vacancy detection using convolution neural networks that give accurate results under any Circumstances.